Efeitos de níveis de nitrogênio sobre o teor de proteína dos grãos de variedades e seleções de arroz - Lima e Silva , Paulo Sérgio; Starling Brandão , Sylvio (Revista Ceres, 2025)
The present study was conducted, under field condition, in order to evaluate the effects of nitrogen fertilizer, applied at the rates of 0, 45, and 90 kg N/ha, on protein content in brown rice and milled rice.